Treading a fine line: (im)possibilities for Nash implementation with partiallyhonest individuals - Michele Lombardi; Naoki Yoshihara (University of Massachusetts, Department of Economics, 2017)
This paper investigates the robustness of Dutta and Sen's (2012) Theorem 1 to weaker notions of truth-telling. An individual honesty standard is modeled as a subgroup of the society, including the individual herself, for which she feels truth-telling concerns. An individual i is honest when she states her true preferences as well as rankings (not necessarily complete) of outcomes that are consistent with the true preferences of individuals in her honesty standard. The paper offers a necessary condition for Nash implementation, called partial-honesty monotonicity, and shows that in an independent domain of preferences that condition is equivalent to Maskin monotonicity.
Keywords: C72; D71; D82; 330; Nash implementation; partial-honesty; non-connected honesty standards; independent domain